Green finance instruments and empowering sustainability in East Asian economies - Yarong Shi; Bo Yang (Humanities & Social Sciences Communications)
Abstract This academic research delves into the effects of the sustainable finance market on the sustainability of the industrial and agricultural sectors across six East Asian economies, utilizing the cross-sectional augmented autoregressive distributed lag (CS-ARDL) model. With East Asia’s heightened vulnerability to climate change, the region exhibits significant potential for sustainability initiatives. Analyzing data from 2000 to 2020, the study uncovers robust correlations between the value of the green finance market and sustainable development in both agriculture and industry. A marginal 1% rise in the green finance market value results in substantial improvements in sustainable development, particularly within the industrial sector. Conversely, CO2 emissions, GDP, and CPI are found to have detrimental effects on sustainability, highlighting the necessity for balanced economic growth and environmental stewardship. In contrast, variables such as the official exchange rate and an educated populace emerge as pivotal drivers of sustainability, underscoring the importance of policy interventions and educational initiatives in fostering environmental responsibility. The policy implications for East Asian economies include the strategic allocation of resources, enhanced education and awareness programs, and the implementation of targeted policies to address environmental challenges.